PENINGKATAN BRANDING DESA WISATA SUNGSANG IV MELALUI PLANG DENAH LOKASI SEBAGAI IKON PROMOSI : IMPROVING BRANDING OF SUNGSANG IV TOURIST VILLAGE THROUGH LOCATION PLAN SIGN AS A PROMOTION ICON - Ellis Nurjuliasti Ningsih; Fauziyah; Fitri Agustriani; Muhamad` Nur; Akhmad Tri Prasetyo (Laporan Upaya Nyata Inovasi Ilmu Komputer, 2025)
The community knows Sungsang IV Village as one of the tourist destinations in Banyuasin Regency. Effective site plan signage helps visitors navigate the tourist area easily and provides important information about key locations such as tourist attractions, public facilities, and other important points. With an attractive and informative design, these site plan signs can be integral to village branding, creating a positive first impression for visitors. Community service aims to increase community knowledge about promotional icons through photo spots and location plans to improve the tourism sector in Sungsang IV Village, Banyuasin Regency, South Sumatra. A field survey was conducted to find out the location of the photo spot and make a sign design given a map of the village location plan. The installation of the sign was carried out in collaboration with the local community. The installation of signs in Sungsang IV Village makes it easy for visitors to access the location and facilities in the tourist village. This activity also improves the identity and promotion of the tourism village, which supports the attraction of local tourism and is expected to impact the economic and social development of the community positively.